On eight species of Chrysillini from Xizang, China (Araneae: Salticidae: Salticinae) - Yang, Zhiyong; Zhang, Junxia (Zootaxa, 2024)
Six new species of Chrysillini are described from Xizang, China: Chrysilla yarlungzangbo sp. nov. (♂), Icius faker sp. nov. (♂♀), I. han sp. nov. (♂♀), I. kui sp. nov. (♂♀), I. kulakangri sp. nov. (♂♀), I. zhengi sp. nov. (♂♀). In addition, a new combination is proposed: Nandicius gyirongensis (Hu, 2001) comb. nov. (♂♀) (transferred from Psenuc Prószyński, 2016), and the males of this species are described for the first time. Siler niser Caleb, Parag & Datta-Roy, 2023 (♂♀) is newly recorded in China.